The Legal Ethics in Financial Technology: How is it Regulated? - Yeheskiel Minggus Tiranda; Lutfi Trisandi Rizki (Jurnal Akta, 2022)
The FinTech sector in ASEAN has grown dramatically. Southeast Asian FinTechs like GoJek and Grab grew from early roots to become digital economy behemoths. New players enter the fray on a regular basis, drawn in by their success and the region's market potential for the people. The purpose of this research is to find out the regulations and ethics of financial law that are used for the welfare of the people. The approach method used was a normative juridical approach, the results of the research result state that: Regulations or laws provide a level of trust, security, and comfort for the community and are something that the state must do without exception as a state of law. One form of protection is the establishment of laws or regulations relating to lending activities, specifically to protect users' rights. To ensure that this process is successful, the state intervenes in the contractual relationship between consumers and business actors, aiming to create a balanced relationship between users and business actors. Funder protection is concerned with protection. Law provided in an effort to obtain goods and services from potential losses due to their use.